2015
DOI: 10.2174/1874306401509010092
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion-Related Acute Lung Injured (TRALI): Current Concepts

Abstract: Transfusion-related acute lung injury (TRALI) is a life-threatening intervention that develops within 6 hours of transfusion of one or more units of blood, and is an important cause of morbidity and mortality resulting from transfusion. It is necessary to dismiss other causes of acute lung injury (ALI), like sepsis, acute cardiogenic edema, acute respiratory distress syndrome (ARDS) or bacterial infection. There are two mechanisms that lead to the development of this syndrome: immune-mediated and no immune- me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 29 publications
0
21
0
1
Order By: Relevance
“…Gando and Otomo [39] have recently described the role of immunothrombosis in acute coagulopathy of trauma shock; they concluded that in trauma patients the mechanism of immunothrombosis and hemostasis is dysregulated and the endothelial injury leads to fibrinogenolysis and subsequent diffuse oozing. Moreover, immunothrombosis and the particular role of extracellular histones have been extensively studied in transfusion-related acute lung injury (TRALI) models [40,41] . However, it seems that, irrespectively of the different pathogenic factors causing ARDS, the inflammatory process is the common pathway triggering the mechanism of microvascular thrombosis.…”
Section: Immunothrombosis In Ards Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Gando and Otomo [39] have recently described the role of immunothrombosis in acute coagulopathy of trauma shock; they concluded that in trauma patients the mechanism of immunothrombosis and hemostasis is dysregulated and the endothelial injury leads to fibrinogenolysis and subsequent diffuse oozing. Moreover, immunothrombosis and the particular role of extracellular histones have been extensively studied in transfusion-related acute lung injury (TRALI) models [40,41] . However, it seems that, irrespectively of the different pathogenic factors causing ARDS, the inflammatory process is the common pathway triggering the mechanism of microvascular thrombosis.…”
Section: Immunothrombosis In Ards Pathophysiologymentioning
confidence: 99%
“…Consequently, neutrophils were activated, with subsequent release of NETs, especially in pulmonary capillaries, resulting in severe lung injury [2] . NETs have also been implicated in the pathophysiology of TRALI, which is one of the most severe complications of transfusion, defined as lung injury developing within 6 h of transfusion of 1 or more units [41] . Animal and human studies concerning TRALI have shown that NETs are found in abundance in the lungs and circulation [40] .…”
Section: Neutrophil Extracellular Trapsmentioning
confidence: 99%
“…In addition, she had no other suspicious gastrointestinal bleeding symptoms such as hematemesis or melena, so the possibility of massive aspiration of bloody vomiting was easily denied. On the other hand, we could not completely distinguish the diagnosis of TRALI, which develops pulmonary edema within six h of transfusion of one or more units of blood , although she had not received a blood transfusion within six h prior to onset of pulmonary hemorrhage. Her hemoglobin level decreased to 3.9 g/dL, the platelet count was 1.5 × 10 4 /μL, the PT was 26%, the INR was 2.59, and the T.Bil elevated to 52.4 mg/dL.…”
Section: Case Reportmentioning
confidence: 80%
“…In most cases, such complication occurs in the passive transfer of alloantibodies originating from donors who have been previously sensitized by leukocyte antigens [8,34]. As an attempt to reduce TRALI risk, ordinance no.…”
Section: Immune Acute Hemolytic Transfusion Reactionmentioning
confidence: 99%